Impact of Type of Surgery on Survival Outcome in Patients With Early Gallbladder Cancer in the Era of Minimally Invasive Surgery: Oncologic Safety of Laparoscopic Surgery. Issue 22 (May 2016) - Jang, Jin-Young; Heo, Jin Seok; Han, Youngmin; Chang, Jihoon; Kim, Jae Ri; Kim, Hongbeom; Kwon, Wooil; Kim, Sun-Whe; Choi, Seong Ho; Choi, Dong Wook; Lee, Kyoungbun; Jang, Kee-Taek; et al.
Abstract : Abstract: Laparoscopic surgery has been widely accepted as a feasible and safe treatment modality in many cancers of the gastrointestinal tract. However, most guidelines on gallbladder cancer (GBC) regard laparoscopic surgery as a contraindication, even for early GBC. This study aims to evaluate and compare recent surgical outcomes of laparoscopic and open surgery for T1(a, b) GBC and to determine the optimal surgical strategy for T1 GBC. The study enrolled 197 patients with histopathologically proven T1 GBC and no history of other cancers who underwent surgery from 2000 to 2014 at 3 major tertiary referral hospitals with specialized biliary-pancreas pathologists and optimal pathologic handling protocols. Median follow-up was 56 months. The effects of depth of invasion and type of surgery on disease-specific survival and recurrence patterns were investigated. Of the 197 patients, 116 (58.9%) underwent simple cholecystectomy, including 31 (15.7%) who underwent open cholecystectomy and 85 (43.1%) laparoscopic cholecystectomy. The remaining 81 (41.1%) patients underwent extended cholecystectomy. Five-year disease-specific survival rates were similar in patients who underwent simple and extended cholecystectomy (96.7% vs 100%, P  = 0.483), as well as being similar in patients in the simple cholecystectomy group who underwent open and laparoscopic cholecystectomy (100% vs 97.6%, P  = 0.543). Type of surgery had no effect on recurrence patterns. Laparoscopic cholecystectomy for T1 gallbladder cancer can provide similar survival outcomes compared to open surgery. Considering less blood loss and shorter hospital stay with better cosmetic outcome, laparoscopic cholecystectomy can be justified as a standard treatment for T1b as well as T1a gallbladder cancer when done by well-experienced surgeons based on exact pathologic diagnosis.